Spiral Limit / Fuziatul Norsyiha Ahmad Shukri ... [et al.] - Ahmad Shukri, Fuziatul Norsyiha; Idris, Nur Azimah; Samsudin, Norshuhada; Wan Mohd Rosly, Wan Nur Shaziayani; Syed Abdullah, Sharifah Sarimah; Mazeni, Noor Azizah (Universiti Teknologi MARA, Kedah, 2023)
Spiral Limit is an educational game designed to assist teachers in creating an enjoyable and engaging learning experience for their students. This game aims to dispel fear and promote excitement about mathematics. Through engaging exercises, it will make mathematics more approachable and thus inspire interest in the topic. It specifically focuses on promoting mental calculation skills, encouraging students to rely less on calculators for simple calculations. This game also offers a fun and creative alternative for students to improve their mathematics skills and strengthen their comprehension of the subject at hand. Teachers act as facilitators, offering assistance to students as needed and allowing them to complete the game independently. Students in their first semesters of university are the main target users for this board game. This game requires at least two players and one moderator. Each player rolls the dice and moves forward according to the number of spaces shown on the dice. Players will need to answer the question correctly within 3 to 5 minutes. If the answer is wrong, the player gets a penalty card. In addition to being used in the classroom, the board game is appropriate for workshops and educational events to spark interest in mathematics. In general, Spiral Limit complements the current educational trend of encouraging active learning, in which students actively engage in the learning process. Overall, Spiral Limit is a valuable tool for teachers to create an engaging and interactive learning experience in calculus. It not only reinforces mathematical concepts but also develops critical thinking, collaboration, and communication skills, all while making the learning process enjoyable for students.